New technologies in libraries and information centres in Latin America and the Caribbean: Information and development - Focus on the Organisation of Eastern Caribbean States (OECS) sub-region - de Freitas, Claudette (1996)
This article examines the history of information systems in the Organisation of Eastern Caribbean States (OECS), proposed development strategy for the area, the OECS INFONET project, and resulting recommendations for developing and sustaining regional information networks. An appendix summarizes 1991 Gross National Product and population data for the Caribbean area
Keywords: INFONET